2015
DOI: 10.5304/jafscd.2015.061.003
|View full text |Cite
|
Sign up to set email alerts
|

Local Food, Food Democracy, and Food Hubs

Abstract: In western North Carolina, where we and others have been working to build local food systems for the last 15 years, food hubs are part of an expanding network of local food distribution infrastructure intended to help the region's smaller local farms access larger, more mainstream market outlets. The impact of food hubs on the region's evolving food system, however, is contradictory. At the same time that food hubs further the development of local food supply chains and create market opportunities for farms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
(68 reference statements)
0
18
1
Order By: Relevance
“…In contrast to research that found local food can bring people in their community together and generate positive social changes (Berlin, Brooks-Gunn, & Aber, 2011;Kato, 2014;NorbergHodge et al, 2002;Perrett, & Jackson, 2015), this study did not find that strengthening social connection was an effective message frame for producing favorable attitudes toward local food. This finding may be an outcome of the indirect and less tangible nature of the concept of the social benefits of bringing people in a community together compared to the concepts of higher food quality and economic benefits.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to research that found local food can bring people in their community together and generate positive social changes (Berlin, Brooks-Gunn, & Aber, 2011;Kato, 2014;NorbergHodge et al, 2002;Perrett, & Jackson, 2015), this study did not find that strengthening social connection was an effective message frame for producing favorable attitudes toward local food. This finding may be an outcome of the indirect and less tangible nature of the concept of the social benefits of bringing people in a community together compared to the concepts of higher food quality and economic benefits.…”
Section: Discussioncontrasting
confidence: 99%
“…Although this study found that a message frame featuring strengthening social connection in a short, online video format was ineffective, previous literature documented consumers' appreciation of social events and the sense of social togetherness local food brought to a community (Norberg-Hodge et al, 2002), and the potential of local food to develop social awareness and democracy (Kato, 2014;Perrett & Jackson, 2015). Further research should explore strategies to communicate the social impact of local food, perhaps not through short videos, but through documentaries, books, workshops, or conferences.…”
Section: Recommendations For Researchmentioning
confidence: 70%
See 1 more Smart Citation
“…Food hubs tend to emerge from a regional context to meet the needs of a specific group of people rooted to a particular place. In most cases, they are based on a general desire to contest the dictates of the corporate, industrial food system and create collective solutions that meet one or more specific needs (Berti & Mulligan, 2016;Perrett & Jackson, 2016;Stroink & Nelson, 2013). Many have physical locations where food is aggregated, processed and/or distributed, while others use internet technology to connect members.…”
Section: Differing Objectivesmentioning
confidence: 99%
“…In this literature, some scholars have questioned the ability of food hubs to meet food-system-change goals. Perrett and Jackson (2016) argue that food hubs are important for linking local food and mainstream markets, but they "alone cannot challenge industry norms and practices, and they can even aid the food industry in maintaining the status quo" (p. 2).…”
Section: Dandymentioning
confidence: 99%